2010
DOI: 10.1111/j.1365-2834.2010.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff teamwork and job satisfaction

Abstract: Aim-The aim of this study was to explore the influence of unit characteristics, staff characteristics and teamwork on job satisfaction with current position and occupation.Background-Teamwork has been associated with a higher level of job satisfaction but few studies have focused on the acute care inpatient hospital nursing team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
181
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(212 citation statements)
references
References 49 publications
15
181
0
5
Order By: Relevance
“…One study demonstrated that teamwork creates a high level of satisfaction and a reduction in mortality rates (23) .…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that teamwork creates a high level of satisfaction and a reduction in mortality rates (23) .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that lower vacancy rates and turnover were associated with a higher level of teamwork while another study showed that when teamwork is good, staff satisfaction is higher (4) . An investigation by Brewer (19) showed that a group-type hospital culture predicted fewer patient falls with injury.…”
Section: Nursing Teamworkmentioning
confidence: 99%
“…Recent work on nursing teamwork has uncovered the importance of teamwork on patient safety and staff satisfaction (2,(4)(5) . No one however has utilized response time to call lights as an indicator of nursing productivity and correlated it to the level of nursing teamwork.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprising, nurses on the medical unit identified coordination as an important factor when collaborating given the care needs of a generally more stable population of admitted patients and a predictable practice setting. [36,37] Although not explained by the quantitative data, a strong theme from the qualitative data was the importance of RNs and RPNs working to their full scope of practice as a facilitator of collaboration. Working to a full scope of nursing practice involves the utilization of theoretical knowledge through the application of critical thinking and clinical skills, [38] and the nurses in the study viewed working to full scope as encouraging collaborative practice.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Collaboration, knowledge and skills are recognized as essential to the successful performance of all healthcare providers, including nurses. [10] As health care professionals, nurses depend on collaboration for the delivery of quality patient care. According to a study done by Lavoie-Tremblay et al, nurses associated a healthy work environment with a culture of respectful and collaborative communication, and social support from colleagues.…”
Section: Introductionmentioning
confidence: 99%